Efek Microwave pada Proses Deasetilasi Kitin dari Limbah Cangkang Udang - Zaeni, Muhammad; Fuadah, Badrotul; Sudiana, I. N. (Jurusan Fisika FMIPA UHO, 2017)
A research about âMicrowave Effect on the Chitin Deacetylation Process of Shrimp-Shell Waste (Panaeus merguensis) â is done. This research aims to decrease the reaction time of acetyl group determination and to get glucosamine hydrochloride that fit the standard. In this research, NaOH 50% is used, while the radiation duration is varied. Microwave radion durations are under 30 minute i.e. 3,7,11,15 minutes with 450 watt power to examine the effectivity of microwave technology compared to conventional method. FTIRÂ (Fourier Transform Infrared)Â test results show that the highest Deacetylation Degree (DD) of chitosan 62,72%, is reached at 15 minutes of microwave radiation duration, that equivalent with deacetylased chitosan by conventional method that is 61,78%. Chitosan then undergoes the making process of glucosamine hydrochloride by using HCl 37%. The characterization result show that glucosamine hydrochloride has a good solubility in water, melting point of 190ÂºC, FTIR spectrum of glucosamine hydrochloride showsÂ absorption bands that fit the standard glucosamine hydrochloride and XRD test result show that theb synthesized crystal still has a low crystalinity.Â Keyword: microwave, chitin, chitosan, deacetylation degree, glucosamine hydrochloride.